Macrolide Use in the Treatment of Critically Ill Patients with Pneumonia: Incidence, Correlates, Timing and Outcomes - Wendy I Sligl; Holly Hoang; Dean T Eurich; Atul Malhotra; Thomas J Marrie; Sumit R Majumdar (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Macrolide antibiotics are commonly used to treat pneumonia despite increasing antimicrobial resistance. Evidence suggests that macrolides may also decrease mortality in severe sepsis via immunomodulatory properties.